Analýza a komparace boxerských stylu elitních amatérských boxeru Kuby a Kazachstánu - Cížek, J. (2020)
Objectives: The main goal of this thesis was to find out whether the frequency of use of punching techniques and the distance from which these punching techniques are used are statistically significant for the style of two the most successful countries in amateur boxing. The countries were compared in the use and success of the strikes and compared to their preference for long or medium combat distance. Methods: The method of quantitative observation was used, in which data was obtained by watching video recordings. Part of the matches was evaluated by recording the results manually on paper, the other part in the BORIS program. All data was then transcribed into a Microsoft Excel spreadsheet, where it was also processed. The source for the data were publicly available video recordings from top competitions in 2010-2020. Results: Differences between countries in the monitored indicators are insignificant and boxing styles do not differ much. In the frequency of the use of striking techniques between the rounds, a significant difference was found only between the first and second round of the Kazakhs. In the case of determining the preference for long and medium distance combat between the rounds, there was a significant difference between the second and third rounds of Kazakh boxers.